Implementing liberal arts education in the era of the Fourth Industrial Revolution: lessons and implications for Korea's higher education policy. (2nd October 2019) - Lee, Yongmo; Moon, Grace Gesoon; Kwon, Young-Kook
ABSTRACT: This paper addresses the role of higher education in the looming era of the Fourth Industrial Revolution. Though some believe that the exponential pace of technological advancement will make traditional higher education obsolete and replace it with lifelong microlearning and upskilling models, research shows that what will empower future generations to thrive in the new age of machines is not up-to-date technical fluency but such distinctly human traits as creative problem-solving, critical thinking, cognitive flexibility, cultural agility, and emotional intelligence. The key to cultivating these soft 'human' skills, the paper contends, lies in liberal arts education. To illustrate how a well-designed liberal arts curriculum can develop the capacities demanded of the future workforce, the paper presents brief case studies of liberal arts programs in Singapore and China. The paper concludes with a discussion of the challenges and policy directions for implementing liberal arts education in Korea's higher education system.